Intralesional cryosurgery in benign vascular lesions: a good option for cherry angioma and hamartomas over port-wine stain - Flávia Trevisan; Dâmia Kuster Kaminski Arida; Laila Djensa Souza dos Santos; Paola Tamara Silva Zakszewski; Fernanda Beatriz Moutinho Zamuner Walger (Sociedade Brasileira de Dermatologia (SBD), 2020)
Cryosurgery is a technique widely known and used among dermatologists. Intralesional application is already used to treat keloids and has the advantage of restricting the zone of action of low temperatures of liquid nitrogen. The use of contact cryosurgery in vascular lesions is well reported in the literature, but there are no intralesional technique publications on these types of lesions. Here, we report two cases, one of port-wine stain hamartomas in a 61-year-old patient and another of a cherry angioma in a 70-year-old patient, safely and satisfactorily treated with intralesional cryosurgery.